Моделювання образу коханої за листами Василя Стуса - Богдан, Світлана Калениківна (Волинський університету ім. Лесі Українки, 2004)
У статті посередництвом епістолярних текстів Василя Стуса реконструюється образ коханої, домінанти її зовнішніх і внутрішніх характеристик, систематизуються визначальні мовні засоби листовного „портретування”. The image of the loved woman, the dominants of her outward and inside characteristics on the base of the Vasyl Stus letters are reconstructed in the article, the main linguistic features of the creating of portrait in the letters are systematized.
The modeling of the image of loved women on the base of the Vasyl Stus letters
Keywords: комунікативна співпраця; комуніканти; стилістика епістолярних діалогів; епістолярний образ адресата; моделювання; communication cooperation; communicants; stylistic of epistolary dialogs; epistolary image of addressee; modeling